Outcome evaluation and cost-effectiveness analysis for an integrated multidisciplinary diabetic limb salvage program: a combined observational and simulation study - Yan Sun; Xiaoli Zhu; Jaime Lin; John Abisheganaden; Zhiwen Joseph Lo; Lixia Ge; Joseph Molina; Elaine Tan; Huiling Liew; Jeremy Hoe; Gary Ang; Kai Qiang Low; et al. (BMJ Open Diabetes Research & Care)
Introduction To compare the clinical outcomes and healthcare utilization of patients enrolled in the multidisciplinary Diabetic Foot in Primary and Tertiary (DEFINITE) Care program with a matched historical cohort and estimate the program’s long-term cost-effectiveness using simulation.Research design and methods This study consisted of two components: a 1-year observational outcome evaluation and a long-term simulation-based cost-effectiveness analysis (CEA). We conducted an observational study to analyze 2798 patients with diabetic foot ulcers (DFUs) enrolled in the program between June 2020 and June 2021 (DEFINITE Care group) and 5462 patients with DFUs from June 2016 to December 2017 as historical controls. One-to-one propensity score matching (PSM) with replacement was conducted to estimate the treatment effect of the program on clinical outcomes and healthcare utilization over 1 year. For the simulation component, a long-term CEA was performed using a Markov state transition model on a simulated cohort of 10 000 patients with DFUs over a 20-year period, assessing transitions between health states, including minor and major amputations and death. The incremental cost-effectiveness ratio (ICER) was calculated for the DEFINITE Care program relative to routine care.Results The estimation of average treatment effects based on propensity scores showed that the DEFINITE Care group exhibited a 9% lower mortality, 5% higher lower extremity amputation (LEA)-free survival, yet a 5% higher minor LEA rate compared with the matched historical controls. Additionally, they experienced fewer inpatient admissions (0.98 fewer episodes) and shorter hospital stays (5.5 fewer days) within 1 year (p-value <0.001). The ICER was US$22 707 (SE: 430) per quality-adjusted life year gained, indicating long-term cost-effectiveness. Probabilistic sensitivity analysis supported these findings.Conclusions The integrated multidisciplinary DEFINITE Care program improved LEA-free survival, reduced inpatient admissions and length of stay within 1 year and demonstrated long-term cost-effectiveness managing DFUs.